Menganalisis Ketimpangan Sosial dan Gender dalam Cerpen Maria Karya Aa Navis Melalui Teori Gayatri Spivak - Rosi Anita Sihombing; Reynaldi Hutapea; Yaszmin Putri Affandi (Universitas Serambi Mekkah, 2025)
This study aims to examine the representation of the struggle of the main female character, Maria, in facing gender inequality through literary works. A descriptive approach and qualitative methods are used to analyze data in the form of words and sentences in short stories that raise the theme of feminism. The results of the study show that Maria is depicted as a strong woman who tries to prove that women can be independent without relying on men. Although her appearance is not striking, Maria has an attractive personality, mature thinking, firm principles, courage, and loyalty to her friends. Maria opposes the view that considers women as weak creatures and dares to fight against male dominance. In addition, she is depicted as a wife who is loyal to her husband.